Feasibility of implementing a supervised telehealth exercise intervention in frail survivors of hematopoietic cell transplantation: a pilot randomized trial - Lee, Kyuwan; Shamunee, Justin; Lindenfeld, Lanie; Ross, Elizabeth; Hageman, Lindsey; Sedrak, Mina S.; Wong, F. Lennie; Nakamura, Ryotaro; Forman, Stephen J.; Bhatia, Smita; Armenian, Saro H. (BMC cancer, 2023)
Background Patients undergoing hematopoietic cell transplantation (HCT) are at high risk of chronic health complications, including frailty and physical dysfunction. Conventional exercise programs have been shown to improve frailty in other cancer populations, but these have largely been based out of rehabilitation facilities that may act as geographic and logistical barriers. There is a paucity of information on the feasibility of implementing telehealth exercise interventions in long-term HCT survivors. Methods We conducted a pilot randomized trial to assess the feasibility of an 8-week telehealth exercise intervention in 20 pre-frail or frail HCT survivors. Participants were randomized to either a telehealth exercise (N = 10) or delayed control (N = 10). We administered a remote physical function assessment at baseline, followed by an 8-week telehealth exercise intervention (30-60 min/session, 3 sessions/week), and post-intervention. The primary endpoint was feasibility as determined by 1) > 70% of participants completing all remote physical functional assessments, and 2) > 70% of participants in the exercise group completing > 70% (17/24) of the prescribed exercise sessions. Exploratory outcomes included changes in gait speed, handgrip strength, and short physical performance battery. Results The mean [standard deviation] age at study enrollment was 64.7 [9.1] years old. Twelve had undergone allogenic and 8 had undergone autologous HCT at an average of 17 years from study enrollment. Both feasibility criteria were achieved. Nineteen patients (95%) completed all remote study outcome assessments at baseline and post-intervention, and nine participants in the exercise group completed > 70% of prescribed exercise sessions. Overall, no significant group x time interaction was observed on handgrip strength, fatigue, body mass index, and short physical performance battery test (P < 0.05). However, there were significant within-group improvements in four-meter gait speed (+ 13.9%; P = 0.004) and 5-minute gait speed (+ 25.4%; P = 0.04) in the exercise group whereas non-significant changes in four-meter gait speed (-3.8%) and 5-minute gait speed (-5.8%) were observed after 8 weeks. Conclusion Implementing an 8-week telehealth exercise intervention for long-term HCT survivors was feasible. Our findings set the stage for innovative delivery of supervised exercise intervention that reduces the burden of frailty in HCT survivors as well as other at-risk cancer survivors. Trial registration The protocol and informed consent were approved by the institutional IRB (IRB#20731) and registered (ClinicalTrials.gov NCT04968119; date of registration: 20/07/2021).